Online Physical Education: Insights from the COVID-19 Pandemic Experiences - Arroyo, Julia Pearl; Salubayba, Teodora (Journal of Interdisciplinary Perspectives, 2024)
The study aimed to explore the online physical education (OLPE) program of a university in Metro Manila during the COVID-19 pandemic. The researcher used a qualitative- case study research design. It focused on providing an in-depth description of the experiences of students and teachers in OLPE courses during the pandemic and analyzing the experiences concerning the achievement of P.E. and physical literacy goals. Interviews with physical education teachers and students were conducted. It also used information from online synchronous P.E. class observations and documents provided by teachers (course packs and syllabi). Results showed that the different components of the learning environment and class design were affected by the sudden shift to online mode and the consequences of the COVID-19 pandemic effects. The OLPE fell short of achieving the NASPE PE Objectives 1 and 4, the development of sport motor skills and the student's sense of responsible personal and social behavior. On the other hand, the OLPE courses achieved NASPE P.E. objectives 2, 3, and 5. These were the student's fitness and health (physical and mental), the value of physical activity for health, and the knowledge of the principles and concepts of fitness and exercise. The results implied that practical online physical education courses must have meaningful two-way communication across all stakeholders, especially between teachers and students; that physical education teachers should collaborate; that teachers and students should meaningfully connect as part of one community, and that fun and enjoyment in P.E. classes should be a priority in designing the class activities within the learning environment.